APLIKASI PENDATAAN PENYEBARAN LAHAN PERTANIAN BERBASIS ANDROID - Firdaus Fajar, Muhammad Rizky; Moh. Anshori Aris Widya; Teguh Priyo Utomo (Computech : Jurnal Ilmiah Teknologi Informasi dan Komunikasi, 2023)
Data on the distribution of agricultural land in Jombang Regency is still relatively low in terms of the accuracy of the location of the land. The information obtained, both owner data and land owned by farmers, will have an impact on regional policies, for example assistance distributed from the government through related agencies and farmer segmentation starting from the middle to lower and upper middle class economic conditions, that's why technology plays a role. information is very important in helping to increase the accuracy of agricultural land data in Jombang Regency. One that can be realized is to make an Android-based data collection application for the distribution of agricultural land in Jombang Regency. By utilizing a smartphone or hand-held cell phone that many people have used today because it is easy to carry and simple. The purpose of this research is to assist Jombang agriculture extension officers in improving the existing system in the hope that the processing and presentation of land data collection is still manual and the system is still not integrated with others can be resolved with the model that the author has developed. The result of making this application is an android-based agricultural land distribution data collection application that integrates with each other with the main website.